Pembelajaran Seni Tari Sebagai Pendidikan Karakter - Syakhruni Syakhruni (Seminar Nasional LP2M UNM, 2019)
Character education has the same essence and meaning as moral education and moral education, supporting the formation of the child's personality, so that children can develop better, citizens, and good citizens. The values of character education can be instilled through many subjects by integrating character values into learning material, and art lessons are no exception. Dance in the world of education, especially junior high schools, has a positive influence. This type of research is a type of research and development (Research and Development). The products produced from this research consist of Syllabus and Teaching Implementation Plan and guidelines that apply to dance teachers or textbooks for learning dance as character education. Analysis of the data obtained in this study were grouped into 3 namely validity, practicality and effectiveness analysis.